2017
DOI: 10.1302/2046-3758.64.bjr-2016-0236.r1
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of tissue-engineered constructs from Acropora and Porites coral in a large animal bone defect model

Abstract: ObjectivesTo compare the therapeutic potential of tissue-engineered constructs (TECs) combining mesenchymal stem cells (MSCs) and coral granules from either Acropora or Porites to repair large bone defects.Materials and MethodsBone marrow-derived, autologous MSCs were seeded on Acropora or Porites coral granules in a perfusion bioreactor. Acropora-TECs (n = 7), Porites-TECs (n = 6) and bone autografts (n = 2) were then implanted into 25 mm long metatarsal diaphyseal defects in sheep. Bimonthly radiographic fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Data also suggests that the tissue-engineered constructs with MSCs (either genetic modified or not) brings us closer to a clinical application. However, nonunion still occurred in nearly half of the bone defects in a large animal model [25]. In fact, the commonly accepted idea that atrophic nonunion is due to lack of MSCs activities of MSCs might be not accurate.…”
Section: Mscs In Nonunion Bone Fracturementioning
confidence: 99%
“…Data also suggests that the tissue-engineered constructs with MSCs (either genetic modified or not) brings us closer to a clinical application. However, nonunion still occurred in nearly half of the bone defects in a large animal model [25]. In fact, the commonly accepted idea that atrophic nonunion is due to lack of MSCs activities of MSCs might be not accurate.…”
Section: Mscs In Nonunion Bone Fracturementioning
confidence: 99%
“…Bone tissue has a certain ability to regenerate. However, large bone defect repairs and complex fracture treatment still present a significant challenge . Moreover, the increasingly aged population has resulted in the requirement for effective therapies for osteoporosis.…”
Section: Hydrogel Scaffold For Regenerative Medicinementioning
confidence: 99%
“…The authors concluded that the presence of MSCs is beneficial for osteoinductive behaviour. A comparation between Acropora or Porite coral granules combined with MSCs for their potential use in bone regeneration was performed by Decambron et al [ 156 ]. The cells were seeded on both types of coral granules, placed in a perfusion bioreactor, and then implanted into bone defects in sheep.…”
Section: Marine-derived Bioceramics As Scaffolds For Bone Tissue Ementioning
confidence: 99%